2015
DOI: 10.1017/s0007114514004371
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics of purified flaxseed and associated mammalian lignans in male Wistar rats

Abstract: Consumption of flaxseed lignans is associated with various health benefits; however, little is known about the bioavailability of purified lignans in flaxseed. Data on their bioavailability and hence pharmacokinetics (PK) are necessary to better understand their role in putative health benefits. In the present study, we conducted a comparative PK analysis of the principal lignan of flaxseed, secoisolariciresinol diglucoside (SDG), and its primary metabolites, secoisolariciresinol (SECO), enterodiol (ED) and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 46 publications
(59 reference statements)
3
34
0
Order By: Relevance
“…Meanwhile, it is reported that the structural analog of anwuligan, was given to rat i.v. at a dose of 20 mg/kg for pharmacokinetic study [27,28], was given to rat i.g. at a dose of 40 mg/kg for pharmacokinetic study [28].…”
Section: Dose Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, it is reported that the structural analog of anwuligan, was given to rat i.v. at a dose of 20 mg/kg for pharmacokinetic study [27,28], was given to rat i.g. at a dose of 40 mg/kg for pharmacokinetic study [28].…”
Section: Dose Selectionmentioning
confidence: 99%
“…at a dose of 20 mg/kg for pharmacokinetic study [27,28], was given to rat i.g. at a dose of 40 mg/kg for pharmacokinetic study [28]. The intravenous dosage of another piece of literature is 20 mg/kg for pharmacological activity study [29].…”
Section: Dose Selectionmentioning
confidence: 99%
“…oily matrices versus cereal bran), lignans are converted to enterolignans by the gut microbiota [20]. Following metabolization, enterodiol and enterolactone may reach a level high enough for signal pathway regulation in the liver, lung, kidney, heart and brain tissues [83] and pharmacokinetic studies show that these microbial metabolites have high systemic clearance and short halflives in the blood circulation, before being excreted as hepatic conjugates with the urine [85]. Dietary consumption of probiotics and limited digestible or indigestible food constituents such as oligosaccharides (prebiotics) and polyphenols or both (synbiotics), regulate the numbers and types of microbes which can influence energy utilization from the diet and regulate energy expenditure and storage.…”
Section: Cereal Lignansmentioning
confidence: 99%
“…The AEA 0-12 h of EL was <2% and tended (P = 0.08) to be lower in H-EL (1.31%) than L-EL calves (1.85%) as shown in Table 1. Interestingly, the oral bioavailability of ED averaged <1% in Wistar rats (Mukker et al, 2015). Low bioavailability of enterolignans may be attributed to poor intestinal permeability or high first-pass metabolism and systemic clearance (Mukker et al, 2015).…”
mentioning
confidence: 99%
“…Interestingly, the oral bioavailability of ED averaged <1% in Wistar rats (Mukker et al, 2015). Low bioavailability of enterolignans may be attributed to poor intestinal permeability or high first-pass metabolism and systemic clearance (Mukker et al, 2015). Guglielmini et al (2012), reported an association between serum EL concentration ≥10 nmol/L and decreased mortality risk (all-causes and breast cancer-specific) in women after breast cancer surgery.…”
mentioning
confidence: 99%